The world oil market in the years ahead : a research paper - United States (Washington : National Foreign Assessment Center, Central Intelligence Agency, 1979)
This report analyzes the outlook study for the world oil market price between 10 July 1979.
Cover title.
"ER 79-10327U, August 1979."
Includes bibliographical references.
asm; 10/04/19
Loans
Keywords: Petroleum industry and trade; Economic forecasting